Sequential persuasion. Issue 2 (13th May 2021) - Li, Fei; Norman, Peter
Abstract : This paper studies sequential Bayesian persuasion games with multiple senders. We provide a tractable characterization of equilibrium outcomes. We apply the model to study how the structure of consultations affects information revelation. Adding a sender who moves first cannot reduce informativeness in equilibrium and results in a more informative equilibrium in the case of two states. Moreover, with the exception of the first sender, it is without loss of generality to let each sender move only once. Sequential persuasion cannot generate a more informative equilibrium than simultaneous persuasion and is always less informative when there are only two states.